If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -10x = 44 + -24x Solving 12 + -10x = 44 + -24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24x' to each side of the equation. 12 + -10x + 24x = 44 + -24x + 24x Combine like terms: -10x + 24x = 14x 12 + 14x = 44 + -24x + 24x Combine like terms: -24x + 24x = 0 12 + 14x = 44 + 0 12 + 14x = 44 Add '-12' to each side of the equation. 12 + -12 + 14x = 44 + -12 Combine like terms: 12 + -12 = 0 0 + 14x = 44 + -12 14x = 44 + -12 Combine like terms: 44 + -12 = 32 14x = 32 Divide each side by '14'. x = 2.285714286 Simplifying x = 2.285714286
| 6+3(5y+2)= | | 4x^2-25x+13=-9x+6 | | 1.2+3.7=34.6 | | 7by=3by-c | | 6(0+y)-5y=23 | | 1x+3(1x+4)=20 | | 2x*33=99 | | 3(x-4)+10=2(x+3) | | 2x*33=54 | | 3[7x-4(x-3)]+1= | | -39-2x=11-7x | | 3(4x+1)+9x= | | 7+3k-2=4k | | 5x-20=95 | | 21(3+y)+8y=-24 | | 4x+7=8x-1 | | 7m^2-3M=0 | | 6x+8=29-x | | 15-3x=1-x | | 9(3x-2)=90 | | c-5=-13+7 | | [2x-3]=5 | | m-.667=1.5m+.333 | | 3(x-4)+10=2(x-3) | | 45n^2+21n=0 | | 25x^2-40x=25 | | 6(2x+2)=36 | | x=-11+20 | | 6n-17p-10n-9p= | | -(x+8)=16 | | -9x+80=16 | | 10(-11+y)-5y=-10 |